Semantic Methods for Execution-level Business Process Modeling Modeling Support Through Process Verification and Service Composition - Weber, Ingo M. (Lecture Notes in Business Information Processing, 2009)
Ingo Weber develops new approaches for the rapid development and flexible adaption of business processes, which are often the main requirements in todays IT support for enterprises. Key issues covered by his work are the automatic composition of processes out of predefined components and the verification of specific process properties. His research aims at quickly creating executable process models, which orchestrate the usage of Web services. He investigates how process modelers can be supported by semantic technologies, e.g., by semantically enriched process models or annotated Web services, and puts special emphasis on expressiveness and scalability.